The Relationship Between Psychological Contract Breach and Organizational Cynicism - Sarikaya, Mehtap; Kok, Sabahat Bayrak (European Scientific Journal, ESJ, 2017)
Psychological contract is composed of employees’ beliefs about what they owe to the organization and what does the organization owe to them in return. However, the psychological contract which is supposed to be between employee and employer and exists in employee’s mind as mutual obligations; is sometimes broken and damaged. When the employer does not fulfill or delayed in fulfilling some obligations, these obligations being either obviously promised or implied, the employee thinks that psychological contract is breached. Organizational cynicism is seen at the employee who perceives a psychological contract breach as a reaction behavior. Organizational cynicism is defined as the negative attitude of an employee towards the organizations (s)he is employed by; which is composed of believing that the organization lacks integration, negative feelings towards the organization, and consistently, humiliating and hypercritical behavior tendency. Organizational cynicism has three dimensions called cognitive, affective and behavioral. In this context, the objective of the research is to reveal the effects of psychological contract breach which is gaining importance for organizations; on organizational cynicism and its dimensions. The data collection method of the research is determined as a survey, and the universe is restricted as research assistants working in a state university. According to the descriptive analysis results, the level of psychological contract breach and organizational cynicism levels of research assistants are low. According to analysis results, psychological contract breach effects both organizational cynicism and its dimensions. Consequently, organizational cynicism increases while psychological contract breach increases.